The Efficacy of Natural Bioactive Compounds for the Treatment of Nasopharyngeal Carcinoma - Huang, Dan-Na; Wang, Shuo; Sooranna, Suren R; Miao, Jian-Hua (Mini Reviews in Medicinal Chemistry, 2021)
The death toll associated with cancer worldwide is constantly on the increase. Efforts to combat and treat the different forms of this disease is also evolving. Nasopharyngeal carcinoma (NPC) is a lethal form of cancer, which is prevalent in Southern China, that is normally treated by using radiotherapy. Here, we will review products obtained from natural sources that have potential cytotoxic and apoptotic properties against NPC. These include grifolin, dihydroartemisinin, luteolin, honokiol, indole-3-carbinol, caffeic acid phenethyl ester, 6-O-angeloylenolin, cucurbitacin E, genistein, helenalin, celastrol, coronarin D, quercetin, trans-cinnamaldehyde, 5'-epimer episilvestrol, silvestrol, arnicolide D, brevilin A, and baicalin hydrate. Ethyl acetate extracts of Wedelia chinensis and aqueous extracts of Ajuga bracteosa are also included although the bioactive compounds involved have yet to be identified. The known mechanism of action of these products is discussed. It is anticipated that one or more of these substances may provide the general population with alternative and cost-effective ways to combat this fatal disease.
Keywords: Cancer